True ferroelectric switching in thin films of trialkylbenzene-1,3,5-tricarboxamide (BTA) - Gorbunov, Andrey V.; Putzeys, Tristan; Urbanavičiūtė, Indrė; Janssen, René A. J.; Wübbenhorst, Michael; Sijbesma, Rint P.; Kemerink, Martijn (Physical chemistry, chemical physics, 2016)
We have investigated the ferroelectric polarization switching properties of trialkylbenzene-1,3,5-tricarboxamide (BTA), which is a model system for a large class of novel organic ferroelectric materials. In the solid state BTAs form a liquid crystalline columnar hexagonal phase that provides long range order that was previously shown to give rise to hysteretic dipolar switching. In this work the nature of the polar switching process is investigated by a combination of dielectric relaxation spectroscopy, depth-resolved pyroelectric response measurements, and classical frequency- and time-dependent electrical switching. We show that BTAs, when brought in a homeotropically aligned hexagonal liquid crystalline phase, are truly ferroelectric. Analysis of the transient switching behavior suggests that the ferroelectric switching is limited by a highly dispersive nucleation process, giving rise to a wide distribution of switching times.
Gesehen am 03.12.2019